Identification of a prefrontal cortex-to-amygdala pathway for chronic stress-induced anxiety - Liu, Wei-Zhu; Zhang, Wen-Hua; Zheng, Zhi-Heng; Zou, Jia-Xin; Liu, Xiao-Xuan; Huang, Shou-He; You, Wen-Jie; He, Ye; Zhang, Jun-Yu; Wang, Xiao-Dong; Pan, Bing-Xing (Nature communications, 2020)
Dysregulated prefrontal control over amygdala is engaged in the pathogenesis of psychiatric diseases including depression and anxiety disorders. Here we show that, in a rodent anxiety model induced by chronic restraint stress (CRS), the dysregulation occurs in basolateral amygdala projection neurons receiving mono-directional inputs from dorsomedial prefrontal cortex (dmPFC→BLA PNs) rather than those reciprocally connected with dmPFC (dmPFC↔BLA PNs). Specifically, CRS shifts the dmPFC-driven excitatory-inhibitory balance towards excitation in the former, but not latter population. Such specificity is preferential to connections made by dmPFC, caused by enhanced presynaptic glutamate release, and highly correlated with the increased anxiety-like behavior in stressed mice. Importantly, low-frequency optogenetic stimulation of dmPFC afferents in BLA normalizes the enhanced prefrontal glutamate release onto dmPFC→BLA PNs and lastingly attenuates CRS-induced increase of anxiety-like behavior. Our findings thus reveal a target cell-based dysregulation of mPFC-to-amygdala transmission for stress-induced anxiety. Dysregulated prefrontal control over amygdala has been implicated in the etiology of stress-related psychiatric disorders. Here, the authors show that the dysregulation preferentially occurs in amygdala neurons that are mono- but not bi-directionally connected with dorsomedial prefrontal cortex.